Redescription of Parapercis macrophthalma (Pietschmann, 1911) and description of a new species of Parapercis (Pisces: Pinguipedidae) from Taiwan - Ho, Hsuan-Ching; Johnson, Jeffrey W. (Zootaxa, 2013)
Parapercis macrophthalma is confirmed as a valid species and redescribed on the basis of the holotype and other specimens collected from the type locality, Taiwan, and Japan. It is morphologically similar to P. muronis Tanaka, 1918, but differs in having five vertical transverse bars that extend well below the lateral line versus five oblique transverse bars, with the third to fifth bars ending on or above the lateral line. A new species is also described on the basis of a specimen collected from southwestern Taiwan. It is distinct in having numerous pores interconnected by canals on the head, forming 10 vertical or oblique rows on the cheek and opercular apparatus, predorsal scales extending to the level of the posterior margin of the eye, four dorsal-fin spines, six oblique bars laterally on the body, and a combination of other characters. A key to species of Parapercis with narrow transverse bars on the upper body is provided.